Tingkat Pengetahuan tentang Kesehatan Gigi Berhubungan dengan Perilaku Perawatan Gigi pada Anak Usia 10-12 Tahun - Syaifurrahman Hidayat; Elyk Dwi Mumpuningtias; Putri Sari Andriyani (Fakultas Kedokteran Gigi Universitas Jember, 2020)
The health of the teeth and mouth aims to prevent the occurrence of holes in the teeth as the main cause of infection in other organs in the oral cavity. Knowledge of parents is a factor that determines oral and dental care behavior early in treating oral and dental health. The purpose of the study was to determine the relationship between the level of knowledge about dental health and dental care behavior in children aged 10-12 years. This type of research was cross sectional. The independent variable was knowledge about dental care and the dependent variable was dental care behavior. One month research time at Banasare 1 Elementary School, Rubaru Subdistrict. Population and sample of all grade IV and V students. The sampling technique used the total population. The research instrument was questionnaire and dental care behavior. Data analysis used Spearman with α (0.05). The results showed that almost all dental health knowledge was good, as many as 40 people (93.0%). Almost all dental care behaviors were good, as many as 40 people (93.0%). The results of data analysis obtained p value = 0,000 with a = 0.005, so p value (0,000) <a (0,005) then H0 is rejected which means there was a relationship between the level of knowledge about dental health and dental care behavior in children aged 10-12 years in SDN Banasare I, Rubaru District. Efforts to improve dental and oral health can be done through health promotion at Banasare Elementary School I. Effective promotion was done by exemplifying how to treat teeth using props continuously every month so that consistency of behavior can be formed and maintained.